Effect of extrusion on folic acid concentration and mineral element dialyzability in Great Northern beans (Phaseolus vulgaris L.). (15th December 2018) - Gulati, Paridhi; Rose, Devin J.
Highlights: Great Northern beans (GNB) are a good source of folate and essential elements. Extrusion significantly improved dialyzability of essential elements in GNB. Extrusion drastically reduced Cd dialyzability. Extrusion resulted in up to 46% reduction in phytate and 24% loss in folate. Extrusion is promising technique for processing of dry beans. Abstract: Great Northern beans (GNB) contain appreciable magnesium (Mg), potassium (K), phosphorus (P), and iron (Fe), together with the heat-labile vitamin, folate, and the anti-nutritional compound phytate. Thus, the objective was to increase dialyzability of essential mineral elements while degrading phytate and minimizing destruction of folate through extrusion of GNB. Extrusion resulted in significant (p < 0.05) increases in dialyzability of Mg, P, K, and Fe by as much as 50%, 30%, 5%, and 79%, respectively, while decreasing cadmium (Cd) dialyzability. Screw speed (SS) had a significant quadratic effect on dialyzability of all elements. Low MC resulted in a significant reduction (46%) in phytate, although this was accompanied by as much as 24% destruction of folate. In conclusion, low barrel temperature, medium MC and high SS were identified as the optimum conditions to maximize essential mineral element dialyzability and folate retention while minimizing phytate and dialyzable Cd.